Susceptibility of weed populations to glyphosate in banana plantations of the Department of Magdalena, Colombia - Quintero-Pertuz,Irma (Instituto de Investigaciones Agropecuarias, INIA, 2021)
ABSTRACT The prevalence and deficient control with glyphosate in some weeds in banana (Musa × paradisiaca L.) plantations in the Department of Magdalena, Colombia, have been evidenced. The susceptibility to glyphosate of prevalent weeds in farms with more than 10 yr of application of this herbicide was evaluated. Seeds and propagules of adult plants of five weedy species were collected from farms where deficient glyphosate control was observed (populations with possible resistance) and in areas not cultivated or free of herbicide use (susceptible populations). Under controlled conditions, seedlings obtained from 17 populations were treated with a commercial dose of glyphosate (1440 g acid equivalent [ae] ha-1) or twice this dose (2880 g ae ha-1). At 21 d after application, populations with a relative fresh weight and survival greater than 20% and visual control lower than 80% were categorized as resistant populations. To determine the resistance factor (RF) in the resistant populations, bioassays were performed with increasing doses of the herbicide (0, 720, 1440, 2880, 5760, and 11 520 g ae ha-1). Populations of Echinochloa colona (L.) Link and Melothria pendula L. were sensitive to both doses, while the populations of Commelina erecta L. and Syngonium podophyllum Schott were not controlled, confirming glyphosate-tolerant. Populations of Erigeron bonariensis L., from uncultivated areas was susceptible, while those from farms were resistant. Glyphosate-resistance was confirmed in two populations of E. bonariensis, with respective RF of 3.5 and 8.6. The repetitive application of glyphosate for weed control in the Magdalena banana farms has contributed to the prevalence of tolerant species and the appearance of herbicide-resistant weeds.